PENGARUH DIVERSIFIKASI OPERASI, LEVERAGE DAN KEPEMILIKAN MANAJERIAL PADA MANAJEMEN LABA - Dimarcia, Ni Luh Floriani Ria; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The purpose of this study was to examine the influence of diversified operations, leverage and managerial ownership on earnings management. The study was conducted on companies listed in the Indonesia Stock Exchange (BEI) 2010-2014. Sample selection technique used is purposive sampling. The data collection is done by the method of documentation and analysis techniques used were multiple linear regression. Based on the results of the study with 65 sample companies observations, it is known that a diversified operation has no effect on earnings management, leverage has no effect on earnings management and managerial ownership negative effect on earnings management.
Keywords: Earnings Management, Diversified Operations, Leverage, Managerial Ownership